Projecting to promote sustainability transitions through joint value creation - Bos-de Vos, Marina; Martinsuo, Miia; Loots, Ellen (Elsevier Ltd, 2025)
Actors involved in programs that promote sustainability transitions project how future value can be created and protected within the constraints of existing institutions and fields. There is a need to better understand this projecting among versatile organizational actors to support the successful advancement of sustainability transitions. Drawing upon the joint value creation employed in five circular economy programs, we identify three modes of projecting for promoting sustainability transitions: distributing, dispersing, and activating. The modes of projecting relate strongly to how programs are configured. We contribute to the sustainability transitions literature by examining niche-regime interactions through the lens of joint value creation, offering novel insights into programs’ unique ways of promoting sustainability transitions. Another contribution is to the literature on value creation in interorganizational projects and programs by revealing different approaches for joint value creation in different modes of projecting.